ANALISIS YURIDIS TINDAK PIDANA PERDAGANGAN ORANG DAN UPAYA YANG PERLU DILAKUKAN DALAM RANGKA PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG - Maria Dita Prasanti (Berajah Journal, 2024)
In principle, human rights are rights inherent in the nature and existence of humans as creatures of God Almighty and are His gifts which must be respected, upheld and protected by the state, law, government and every person for the sake of honor and protection of honor and dignity. The criminal act of human trafficking is a form of human rights violation that must be eradicated. This research aims to obtain analysis results regarding the regulation of criminal act of human trafficking in Indonesia and efforts that can be made to eradicate criminal act of human trafficking. The research method used is normative legal research with a statutory approach. Based on the results of the analysis, it was concluded that there are statutory provisions relevant to the criminal act of human trafficking, including Law No, 39 of 1999, Law No. 21 of 2007, Law No. 5 of 2009, and Presidential Decree No. 69 of 2008 and its amendments. However, even though there are statutory provisions governing the criminal act of human trafficking, there are still many cases of criminal act of human trafficking that occur in Indonesia. Therefore, it requires the participation of all elements, including the government, law enforcement officers and the community, to make efforts to prevent, prosecute, and eradicate the criminal act of human trafficking.